Influence of Classroom Misconduct on Academic Performance of Senior Phase Learners: The Teachers’ Perspectives - Khantsi, Moneilweng P.; Okeke, Charity C.; Akobi, Thomas Ogbeche (CV. Literasi Indonesia, 2024)
Classroom misconduct among students continues to be a challenge, particularly for South African teachers. Senior phase learners in South African schools have demonstrated an alarming amount of misconduct in classroom settings, and this tends to affect students' academic performance as it disrupts the process of teaching and learning. In this study, the researchers tried to examine the perceptions of teachers on the causes of classroom misconduct among senior phase learners in South Africa and how it influences their academic performance. The study adopted a qualitative research approach and employed a phenomenological research design. The sample of the study comprised 12 high school teachers purposefully selected to participate in the study. The data were collected through semi-structured interviews and analyzed using thematic analysis. Findings revealed that learners' background, attention-seeking, child-headed responsibilities, and teachers’ unpreparedness and inconsistency are among the causes of classroom misconduct among senior phase learners. It was found also that students’ classroom misconduct hinders the teaching and learning process in the classroom, and also interferes with other learners’ learning disrupts the whole process of teaching and learning, and in the long run, affects the academic performance of students. Based on these findings, the study recommended that teachers should give learners full attention at school to reduce distractions in the classroom. The study further recommends that teachers should be professional and serious in handling teaching and learning matters to keep learners busy, this will help to reduce the rate of misconduct among senior phase students.